Report on the Neilgherry Loranthaceous Parasitical Plants Destructibe to Exotic forest and Fruit Trees- By George Bidie, M. D., Surgeon-Major, Superintendent, Government Central Museum, Madras - , J. S. G. (Indian Forester)
No abstract